Analysis of Viscosity of Lubricating Oil on Generator Machine Working Hours at KP. Macan Tutul 4203 - Ade Hermawan; Istianto Budhi Rahardja; M Yusuf Syam; Hendro Sukismo; Nur Fatah; Mardiono Mardiono (Faculty of Engineering Universitas Muhammadiyah Jakarta, 2019)
Lubricating oil is a liquid used as a lubricant in a machine to reduce wear due to friction, and as a coolant and silencer, but high temperatures on the engine will damage the lubricant. When the lubricant power is reduced, the friction will increase and then the heat will arise more and more so that the temperature continues to increase. Engine oil should have high viscosity or viscosity, not inflammable not easy to oxidize and not frothy due to high rotation that occurs inside the machine. other than that lubricating oil serves to protect the inside of an engine parts from rust or corrosion caused by liquids in lubricants and acid properties which are the result of high temperature combustion in the machine. The purpose of this research is to know the viscosity and content contained in lubricant oil of Meditran sx plus SAE 15W-40 in hours of use 50,100,150 and 200 hours of machine work with laboratory test method. The results obtained in the laboratory test viscosity of new lubricant oil is 14.55 cSt to the use of lubricating oil 50 hours of machine work, then the use of lubricating oil 100 hours working machine, there has been a decrease in viscosity from 13.15 cSt to 12.85 cSt and on usage lubricating oil 150 working hours fixed viscosity of 12.85 cSt then on the use of lubricating oil 200 hours of work decreased viscosity to 12.62 cSt.